The political and civic implications of Chicago`s unsuccessful bid to host the 2016 Olympic Games - Bennett, L.; Bennett, M.; Alexander, S.; Persky, J. (Journal of Sport and Social Issues, 2013)
This article investigates how "war-speak" is incorporated into both sports media coverage and athletic rituals. It posits that while the militarization of American sporting events may help to comfort a nation in crisis and afford the Armed Forces a valuable recruitment tool, it simultaneously encourages a coercive patriotism that is morally problematic for many athletes and fans, especially during wartime. Likewise, although the use of war metaphors in sports media coverage provides exciting and dramatic language for players and sportscasters, it also devalues the war experience by trivializing its horrors and helps to sell the concept of war as sport.